Kepemimpinan pendidikan islam (Kepemimpinan Berjiwa Kewirausahaan dalam Bidang Pendidikan di Era Society 5.0) - Maulani, Kharisma (Maliki Interdisciplinary Journal, 2025)
This research seeks to investigate the entrepreneurial leadership exhibited by school principals, focusing on the defining characteristics of such leadership within the educational sector in the context of contemporary society. The application of entrepreneurial leadership within the educational sector in the context of contemporary society. This research methodology employs a qualitative framework, utilizing a literature review as its primary approach. This research employs secondary data sourced from e-books, academic journals, and online literature pertinent to the field of entrepreneurial leadership. The results of this research show: 1) the characteristics of entrepreneurial leadership in the field of education in the era of society are leaders who have innovative and creative thinking, leaders who work hard and leaders who have strong motivation. The execution of entrepreneurial leadership within the educational sector in contemporary society involves the advancement of curriculum innovation, the empowerment of educators, the integration of technology, and the establishment of partnerships with the business community.